Identification of mutations in the HVR1 and PKR-BD regions in HCV-infected patients resistant to PEG-IFNα/RBV therapy - Holysz, M. (J Appl Genet, 2015)
The identification of mutations in the HVR1 region of hepatitis type C virus (HCV) is time-consuming and expensive, and there is a need for a rapid, inexpensive method of screening for these mutations to predict the ineffectiveness of pegylated interferon alpha combined with ribavirin (PEG-IFNα/RBV) therapy. The project was designed to evaluate the usefulness of the high resolution melting (HRM) technique to screen for mutation in the cDNAs encoding the HVR1 and protein kinase R-binding domain (PKR-BD) regions in a group of 36 patients infected with HCV and resistant to 12 months of combined therapy with PEG-IFNα/RBV. Viral RNA was isolated, reverse transcribed, and the fragments encoding the HVR1 and PKR-BD regions were polymerase chain reaction (PCR)-amplified, cloned, sequenced, and the melting profiles and the melting temperature (T(m)) were determined by the HRM technique. After the treatment, the melting profiles of HVR1 cDNAs revealed a dominant peak corresponding to the T(m) of about 85 °C (HCVs85) in almost all patients. One or more minor peaks were also observed, indicating the existence of cDNA(s) of different T(m). The HMR analysis suggested four typical forms of response to treatment. These suppositions were supported by sequencing. The HRM analysis revealed no changes in the melting profiles of PKR-BD cDNAs in the same patient before and after the therapy, suggesting that, within 12 months of treatment, new mutations were not introduced in PKR-BD. These findings were substantiated by sequencing. The HRM technique can be applied for the rapid screening for mutations in the cDNAs encoding the HVR and PKR-BD regions of HCV. We suggest that the detection of HCVs85 peak before the IFNα/RBV therapy might predict the ineffectiveness of treatment.